Madura's Local Wisdom in a Global Context: Developing an E-Book to Foster Critical Thinking on Climate Issues - Madani, Lutfi; Raharjo, Raharjo; Purnomo, Tarzan (LPPM Universitas Pendidikan Mandalika, 2025)
This research aims to produce a valid and effective problem-based learning e-book integrated with Madura's local wisdom to enhance students' critical thinking skills. This study employed a Research and Development (R&D) method with the ASSURE model, which includes the stages: analyze learner characteristics, state objectives, select, modify or design media, utilize media, require learner response, and evaluate. The subjects of this research were 20 students from class X at State Senior High School 4 Bangkalan, Madura Regency. The research instruments used included expert validation sheets, observation sheets for learning implementation, pre-test and post-test critical thinking skills, and student response questionnaires. Data analysis used the quantitative descriptive method. The research results show that this problem-based e-book received a high validity index score in terms of content feasibility, presentation, and language, categorizing it as valid with an average score of 3.13. The implementation of learning achieved a high percentage score of 80% with practical criteria. Based on post-test results, 90% learning completeness was obtained. The N-Gain pretest-posttest calculation results indicate an average N-Gain score of 0.71 with high criteria. The improvement in critical thinking indicator achievement had an average N-Gain score of 0.78, and the positive response from students towards the use of the e-book reached 90.76% with very good criteria. The results of this study affirm that the problem-based e-book integrated with Madura's local wisdom is capable of significantly enhancing students' critical thinking skills.